Magnetodielectric Effects in Magnetorheological Elastomers Based on Polymer Fabric, Silicone Rubber, and Magnetorheological Suspension - A. M. Gavrilovici; E. M. Anitas; L. Chirigiu; I. Bica; M. L. Negrutiu (Advances in Polymer Technology)
We fabricate a hybrid magnetorheological elastomer (hMRE) based on a microfiber cloth soaked with a mixture containing magnetorheological suspension (MRS) and silicone rubber (SR). Two parallel copper electrodes are attached to the hMRE and the capacitance C is measured as a function of time t, for fixed values of magnetic flux density B. We show that C is stable in time and is sensibly influenced by B, while the relative dielectric permittivity increases up to two orders of magnitude when B reaches 340 mT. We explain the physical mechanism which leads to the observed magnetodielectric effects. The obtained results can be used for various biomedical applications such as in fabrication of active biomagnetic membranes used in dental implantology.